(untitled) (Journal of the College of Basic Education, 2022)
Jokes can create an occasional picture of the world .It can break the known common script, violate norms or pushes them together .The interesting thing about jokes is the fact that they form some kind of altering of the logicality of our thinking. Humor has always been a part of military life. Within the military , under the stress of military operations or training, spontaneous humor is a way to deal with the pressure and form bonds of common experience. Therefore, there is a huge body of humorous stories, cartoons, as well as songs and shows by comedians, all with the military as the theme and subject matter. Service members and intelligence personnel always submit their comic musings to Reader`s Digest and such musings are usually published in a popular section entitled ( Humor in Uniform) which feeds from real and actual incidents , because humor is still the best way to cope with the stress of events. And since lexical ambiguity is the core of language - based jokes, this paper examines and reviews this ambiguity and the humorous effect presented by ( homonymy, paronym and polysemy). A joke can be a helpful tool in the process of teaching and learning foreign languages .It is conducive and essential to learning as well as providing the language, definitions of linguistic phenomena and illustrating them with examples easy to understand and memorize.